Suitability of California bay laurel and other species as hosts for the non‐native redbay ambrosia beetle and granulate ambrosia beetle. (27th March 2013) - Mayfield, Albert E.; MacKenzie, Martin; Cannon, Philip G.; Oak, Steven W.; Horn, Scott; Hwang, Jaesoon; Kendra, Paul E.
Abstract The redbay ambrosia beetle Xyleborus glabratus Eichhoff is a non‐native vector of the pathogen that causes laurel wilt, a deadly disease of trees in the family Lauraceae in the southeastern U.S.A. Concern exists that X. glabratus and its fungal symbiont could be transported to the western U.S.A. and cause damage to California bay laurel Umbellularia californica (Hook. & Arn.) Nutt. in California and Washington. The present study evaluated in‐flight attraction, attack density and emergence of X. glabratus and another invasive ambrosia beetle Xylosandrus crassiusculus (Motschulsky) on cut bolts of California bay laurel and eight related tree species in an infested forest in South Carolina. Xylosandrus crassiusculus is not a vector of the laurel wilt pathogen but is a pest of nursery and ornamental trees. Mean catch of X. glabratus on California bay laurel bolts was not significantly different from catches on bolts of known X. glabratus hosts sassafras Sassafras albidum (Nutt.) Nees and swampbay Persea palustris (Raf.) Sarg. Mean attack density and adult emergence of both beetle species from California bay laurel was equal to or greater than all other tree species tested. Both beetle species readily produced brood in California bay laurel bolts. The results obtained in the present study suggest that California bay laurel may be negatively impacted by both of these invasive ambrosia beetles if they become established in the tree's native range.